Impact of persistent smoking on long-term outcomes in patients with nonvalvular atrial fibrillation. Issue 5 (May 2015) - Nakagawa, Keiko; Hirai, Tadakazu; Ohara, Kazumasa; Fukuda, Nobuyuki; Numa, Satoshi; Taguchi, Yoshiharu; Dougu, Nobuhiro; Takashima, Shutaro; Nozawa, Takashi; Tanaka, Kortaro; Inoue, Hiroshi
Abstract: Background: Although smoking is a risk factor for cardiovascular diseases, little is known about the impact of smoking on long-term outcomes in patients with atrial fibrillation (AF). Methods: In 426 consecutive patients with nonvalvular AF (mean age, 66 years; 307 men; mean follow-up, 5.8 ± 3.2 years), clinical variables including smoking status, CHADS2, and CHA2 DS2 -VASc score, incidences of cardiovascular events (stroke, myocardial infarction, or admission for heart failure), bleeding, and mortality were determined. Results: Incidences of intracranial bleeding (0.7% vs 0.1%/year, p  < 0.01), all-cause mortality (4.9% vs 2.6%/year, p  < 0.01), and death from stroke (0.8% vs 0.2%/year, p  < 0.05) were higher in patients with history of smoking than in those without it. Incidence of intracranial bleeding was significantly higher in persistent smokers than in non-persistent smokers (1.2% vs 0.2%/year, p  < 0.01). History of smoking predicted all-cause mortality [hazard ratio (HR), 2.7; 95% confidence interval (CI), 1.7–4.5; p  < 0.01] and death from stroke (HR 4.7; 95% CI 1.0–22.3; p  < 0.05) independent of age, antithrombotic treatment, CHADS2, and CHA2 DS2 -VASc score. Persistent smoking predicted intracranial bleeding (HR 4.4; 95% CI 1.1–17.6; p  < 0.05) independent of age and antithrombotic treatment. Conclusions: Smoking status, independent of age, antithrombotic treatment, and clinical risk factors, predicted long-term adverse outcomes including bleeding events in patients with nonvalvular AF. There might be an obvious impact of persistent smoking on intracranial bleeding.